Case Report: Intravascular Papillary Endothelial Hyperplasia In An Older Man - POPA, ANDREEA; ILIE, LACRAMIOARA; MIHALACHE, DANIELA; GURAU, ALINA MIHAELA; MIRCEA, MIOARA; BALAN, OANA MARIA; BALTA, ALEXIA ANASTASIA; AMBROSE, LENUTA; CRISTINA, CHELMU; GRIGORE, IONICA; MAFTEI, NICOLETA MARICICA; MEHEDINTI, MIHAELA CEZARINA (Technium BioChemMed, 2023)
Masson's tumor is a benign tumor consisting of reactive proliferation of endothelial cells. It was first described by the French doctor, Pierre Masson, in 1923. A higher incidence was observed among women (1.3:1), and the average age at which it occurs is 31 years. It appears as a firm mass, with the appearance of a nodule or papule, located subcutaneously. The adjacent integument is bluish or reddish. On palpation it can be sensitive or painless. We will present the case of an 81-year-old man with Masson's tumor located at the level of the volar side of the left forearm, at the level of the flexor ulnar muscle of the carpi, which affects the ulnar artery.